EGOCENTRIC LEADERSHIP: REAWAKENING AFRICAN MORAL CONSCIOUSNESS USING ACHEBE’S ARROW OF GOD - Ogbonnaya, Ejie Ifeoma (The Melting Pot, 2021)
To reduce the high level of poverty, insecurity and moral decadence in African society, African leaders need to hold tight to the African moral standard that helps to make critical decision and the people’s needs, a priority. This moral standard is the aspect of leadership that will enhance the socioeconomic growth of Africa and hinder the manipulative neo-colonial ideologies from getting a full grip of Africa’s socio-cultural consciousness that prioritizes the community over self. Some of the neocolonial ideas present themselves in the form of selfishness, materialism and a quest for superiority. The two main characters in Achebe’s Arrow of God; Ezeulu and Nwaka, were leaders who allowed their egocentric nature to take upper hand in their decisions and actions which resulted into various crises and socioeconomic backwardness. The text therefore, uses the psychological concept of egoism to analyze the extent of damage caused by egocentric leadership in the text of our study and how it relates to the plight of the present day African society and through that call for the reawakening of the African moral consciousness in the leaders.